(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides foreign experience in the development of the social sphere of enterprises, the maindirections for the development of the concept of social partnership between the state and businessin foreign countries. A number of conclusions are also given based on analyzes of foreign experience in the development of the social sphere of enterprises.